2023
DOI: 10.21203/rs.3.rs-2772282/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Introducing MR-TADF Emitters into Light-Emitting Electrochemical Cells for Narrowband and Efficient Emission

Abstract: Organic semiconductors that emit by the process of multi-resonance thermally activated delayed fluorescence (MR-TADF) can deliver narrowband and efficient electroluminescence while being processable from solvents and metal free. This renders them attractive for use as the emitter in sustainable light-emitting electrochemical cells (LECs), but so far reports on narrowband and efficient MR-TADF emission from LEC devices are absent. Here, we address this issue through careful and systematic material selection and… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…[32] The color purity of these results was better than that of recently reported LECs with MR-TADF emitters. [33,34] Therefore, we concluded that the realization of ultrapure blue EL emissions based on solution-processable LECs could contribute greatly to the creation of a sustainable society in the future.…”
Section: Device Performancesmentioning
confidence: 93%
See 1 more Smart Citation
“…[32] The color purity of these results was better than that of recently reported LECs with MR-TADF emitters. [33,34] Therefore, we concluded that the realization of ultrapure blue EL emissions based on solution-processable LECs could contribute greatly to the creation of a sustainable society in the future.…”
Section: Device Performancesmentioning
confidence: 93%
“…The serious issue of low external quantum efficiency (<1% for both LECs, Figure S15, Supporting Information) and operational stability (Figure S16, Supporting Information) remains to be addressed; however, there are many recently proposed improvement methods that can solve this problem in the future. [34][35][36][37]…”
Section: Device Performancesmentioning
confidence: 99%